Three-mode optical thermometer based on Ca3LiMgV3O12:Sm3+ phosphors. Issue 10 (15th May 2023) - Chen, JianQuan; Chen, JunYu; Zhang, WenNa; Xu, ShuJun; Chen, LiPing; Guo, Hai
Abstract: A series of Ca3- x LiMgV3 O12 : x Sm 3+ (CLMV:Sm 3+ ) phosphors were elaborated to provide new optical temperature sensing materials. Their structures, morphologies, and luminescent properties were comprehensively explored. The energy transfer from VO4 3− to Sm 3+ was illustrated using luminescent spectra and luminescent decay curves. The different temperature dependent emission and excitation characters of VO4 3− group and 4f-4f transition of Sm 3+ were used to design a three-mode optical temperature sensor. Temperature dependent fluorescence intensity ratio ( FIR ) value of I (Sm 3+ ) and I (VO4 3− ), Commission International de L'Eclairage (CIE) coordinate, and excitation intensity ratio ( EIR ) value of I 383nm / I 405nm in excitation spectra are the three sensing modes. The maximum value of absolute sensitivity ( S A ) and relative sensitivity ( S R ) in FIR mode are 9.11 %K −1 at 513 K and 1.99 %K −1 at 357 K, respectively. And S R is bigger than 1.21 %K −1 between 303 and 513 K, which is superior to that of thermometry based on Er 3+ doped upconversion phosphors. The maximum S R in EIR mode is 1.39 %K −1 at 393 K. Our results indicate that CLMV:Sm 3+ phosphors might have potential application as optical thermometry with self-reference character.